2011
DOI: 10.1089/gtmb.2010.0159
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ethnicity-Specific Sequence Tag Site Markers for Y Chromosome Microdeletion Studies

Abstract: The markers prescribed by EAA alone are not suitable for the diagnosis of Y chromosome microdeletions in infertile males. The protocol for identification of Y chromosome microdeletions in cases of nonobstructive azoospermia/severe oligospermia would have to include a different set of STS markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…However, there have been growing concerns regarding the use of only these six markers considering the heterogeneity in the Yq sequences in different populations. Indeed, studies have shown high frequency of false negativity when only the six EAA markers have been used for analysis [26]. While no association was observed between the number of STS markers used for testing and the frequency of microdeletions, to test if only the EAA markers are sufficient in detecting the microdeletions in the Indian population, we compiled the data from studies were along with EAA, other markers (now on referred to as non-EAA markers) were used for detection of Yq microdeletions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there have been growing concerns regarding the use of only these six markers considering the heterogeneity in the Yq sequences in different populations. Indeed, studies have shown high frequency of false negativity when only the six EAA markers have been used for analysis [26]. While no association was observed between the number of STS markers used for testing and the frequency of microdeletions, to test if only the EAA markers are sufficient in detecting the microdeletions in the Indian population, we compiled the data from studies were along with EAA, other markers (now on referred to as non-EAA markers) were used for detection of Yq microdeletions.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond sample size and ethinicity, the markers used for microdeletion testing also influence the frequency. Yq microdeltion testing by PCR involves use of several unique Sequence Tag Site (STS) markers which are a determinant of the sensitivity and specificity for detection of deletions [26,28]. In the studies published from India, the numbers and types of STS markers used by different authors for detection of Yq microdeletions are not uniform, in some instances very limited and/or non conventional markers have been utilized [14,17,36] which could also be a possible reason for the observed variations.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have good methodological accuracy. The sample universe is quite heterogeneous, given the very design of the studies (22 case reports with 02 individuals up to 33 cross-sectional studies with 4, 441 individuals), age differences between individuals in the samples ranging from 17 years [10] to 66 years [21], as well as the origin of the patients who were: India [2,23,25,35], Brazil [3,31,34,36], China [4,10,17,18], Iran [1,7,19,21] Turkey [5,26,27] [20], Denmark [37], USA [22], england [38], Mexico [30], Serbia [28] and Venezuela [32]. Because of this situation, the data becomes divergent and the comparative analysis becomes troublesome.…”
Section: Resultsmentioning
confidence: 99%
“…al. [2] detected by analyzing 200 infertile men in India, microdeletions in 21 (10.5%). Among them, 13 were in cases of azoospermia and eight in cases of severe oligozoospermia.…”
Section: J Med Genetmentioning
confidence: 99%
See 1 more Smart Citation